Study on the surface-modification for nano-hydroxyapatite with 12-hydroxystearic acid and the reinforcing effect for poly(lactic-o-glycolide) - H. J. Ding; S. Tang; L. Y. Jiang; B. L. Ma; C. Y. Tang; S. P. Su (eXPRESS Polymer Letters, 2020)
In this paper, 12-hydroxystearic acid was used to modify the surface nano-hydroxyapatite(n-HA) by co-precipitation method or blending method. Fourier transformation infrared (FTIR), X-ray diffraction (XRD), intuitionistic dispersion, transmission electron microscope (TEM) and thermal gravimetric analysis (TGA) showed that the blending method confirmed 12-hydroxystearic acid was successfully grafted on the surface of n-HA, which endowed n-HA with better dispersion in hydrophobic solvents, and the dispersion was improved with the addition amount of 12-hydroxystearic acid. Correspondingly, it exhibited better improvement for poly (lactic-o-glycolide)(PLGA), owing to better interface adhesion in PLGA matrix and promotion crystallization by investigating the tensile strength, fracture morphology, polarized optical microscopy (POM), differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA) of the composites. Especially, the tensile strength was 23.81% higher than that of pure PLGA when 5 wt% n-HA was added, suggesting the obtained n-HA was promising to improve the mechanical strength of PLGA. Moreover, in vitro cell culture, experimental results indicated that n-HA/PLGA composites displayed better cell biocompatibility. Taken together, these results demonstrated that the introduction of 12-hydroxystearic acid by blending method was a novel method to modify the surface of n-HA, which has a great potential to obtain ideal n-HA/PLGA composite as bone materials.